Nuclear receptor-SINE B1 network modulates expanded pluripotency in blastoids and blastocysts - Ka Wai Wong; Yingying Zeng; Edison Tay; Jia Hao Jackie Teo; Nadia Omega Cipta; Kiyofumi Hamashima; Yao Yi; Haijun Liu; Tushar Warrier; Minh T. N. Le; Soon Chye Ng; Qi-Jing Li; et al. (Nature Communications)
Abstract Embryonic stem cells possess the remarkable ability to self-organize into blastocyst-like structures upon induction. These stem cell-based embryo models serve as invaluable platforms for studying embryogenesis and therapeutic developments. Nevertheless, the specific intrinsic regulators that govern this potential for blastoid formation remain unknown. Here we demonstrate an intrinsic program that plays a crucial role in both blastoids and blastocysts across multiple species. We first establish metrics for grading the resemblance of blastoids to mouse blastocysts, and identify the differential activation of gene regulons involved in lineage specification among various blastoid grades. Notably, abrogation of nuclear receptor subfamily 1, group H, member 2 (Nr1h2) drastically reduces blastoid formation. Nr1h2 activation alone is sufficient to rewire conventional ESC into a distinct pluripotency state, enabling them to form blastoids with enhanced implantation capacity in the uterus and contribute to both embryonic and extraembryonic lineages in vivo. Through integrative multi-omics analyses, we uncover the broad regulatory role of Nr1h2 in the transcriptome, chromatin accessibility and epigenome, targeting genes associated with embryonic lineage and the transposable element SINE-B1. The Nr1h2-centred intrinsic program governs and drives the development of both blastoids and early embryos.